Digitalization of revenue mobilization in an emerging economy: the new Institutional Theory perspective - Nora Agyei-Ababio; Eric Ansong; Kwame Assa-Agyei (International Journal of Information Systems and Project Management, 2023)
This study sought to explore how the institutional environment comprising regulative, normative, and cognitive factors influences the use of technology in revenue mobilization in the public sector of an emerging economy. The study used the new institutional theory as a theoretical lens and a qualitative case study as a methodological stance. Data was collected from the agency in charge of revenue mobilization in the developing economy through interviews. The study established that regulative, normative and cognitive factors influence the digitalization of revenue mobilization. With regards to the regulative pillar, it was revealed that legislation for a revenue authority with a focus on digitalization, legislation for taxpayer identification and legislation for electronic transactions were laws that governed the use of the system and played essential roles in ensuring that the system was used effectively to fully realize its benefits. The cognitive pillar, on the other hand, revealed some challenges faced with the implementation and use of the digital system. The study contributes to the literature on the digitalization of revenue mobilization, which has arguably seen very few studies conducted in Africa, especially in Ghana, hence calling for more future studies on the use of e-revenue systems in developing economies.